Team player tracking using sensors and signal strength for indoor basketball - Kirkup, J. A.; Rowlands, D. D.; Thiel, D. V. (IEEE Sensors Journal, 2016)
Wireless tracking of players for indoor team sports can provide information for both coaching assistance and individual improvement. Body worn accelerometer sensors have been used extensively to monitor and provide information such as body movements and heart rate. By also employing a beacon valuable data like player positioning and offensive play checks in the game of basketball can be provided using radio-frequency interference (RF) signal positioning techniques. Positional accuracy from a previous study using uncertainty ellipses, not yet published, shows signal variations of 3 dB having little impact on the position estimation error for a single player. The introduction of multiple moving players in the vicinity to the player worn beacon shows a variation (with no obstruction) of < 3 dB for a distance of 5.5 m confirming a minimal impact from multipath interference. This equates to a localization error of ~1 m or less. In depth fading studies show favorable statistical results. Previous sensor accelerometer studies show that a unique signal pattern can be used to determine if a player is bouncing the ball. Further investigation in this study shows this can also be applied to passing the ball. A prototype player tracking system was tested and confirmed wireless RF signal tracking of offensive players is viable. The results of this study can be used in design considerations for other systems employing wearable wireless sensors and beacons to estimate position and body actions for team players in basketball and potentially other sports within the indoor environment. AUTORREFERAT